The Mitotic Spindle Methods and Protocols - Chang, Paul.; Ohi, Ryoma; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Humana Press, 2016)
This volume includes a series of protocols focused on mitotic spindle assembly and function. The methods covered in this book feature a broad range of techniques from basic microscopy to the study of spindle physiologies relevant to cancer. These methods can be applied to diverse model systems that range from the cell-free Xenopus egg extract system to the moss Physcomitrella patens, in an effort to demonstrate the key contributions made by researchers using multiple model organisms. Chapters in The Mitotic Spindle: Methods and Protocols integrate cutting-edge technologies that have only become available due to the cross-disciplinary efforts, such as ATP analogue sensitive inhibition of mitotic kinases. Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls. Thorough and informative, The Mitotic Spindle: Methods and Protocols, is a valuable resource for researchers who are new to mitosis or are already experts in the field. .
Using Fluorescence Microscopy to Study Mitosis -- Using Photoactivatable GFP to Study Microtubule Dynamics and Chromosome Segregation -- Purification and Fluorescent Labeling of Tubulin from Xenopus Laevis Egg Extracts -- Measuring the Effects of Microtubule-Associated Proteins on Microtubule Dynamics In Vitro -- Imaging and Quantifying the Dynamics of gc(B-Tubulin at Microtubule Minus Ends in Mitotic Spindles -- Visualizing and Analyzing Branching Microtubule Nucleation Using Meiotic Xenopus Egg Extracts and TIRF Microscopy -- Encapsulation of Xenopus Egg and Embryo Extract Spindle Assembly Reactions in Synthetic Cell-Like Compartments with Tunable Size -- In Vitro Kinetochore Assembly -- Biochemical and Structural Analysis of Kinetochore Histone-Fold Complexes -- Measuring Kinetochore-Microtubule Attachment Stability in Cultured Cells -- Studying Kinetochores In Vivo Using FLIM-FRET -- Purification of Fluorescently Labeled Saccharomyces Cerevisiae Spindle Pole Bodies -- A Cell-Free System for Real-Time Analyses of Centriole Disengagement and Centriole to Centrosome Conversion -- Assays to Study Mitotic Centrosome and Spindle Pole Assembly and Regulation -- Analyzing Spindle Positioning Dynamics in Cultured Cells -- Quantification of Mitotic Chromosome Alignment -- Imaging Mitosis in the Moss Physcomitrella Patens -- Small Molecule Approach to Study the Function of Mitotic Kinesins -- Identification and Characterization of Mitotic Spindle-Localized Transcripts -- Probing Mitosis by Manipulating the Interactions of Mitotic Regulator Proteins Using Rapamycin-Inducible Dimerization -- Studying Kinetochore Kinases -- Engineering and Functional Analysis of Mitotic Kinases through Chemical Genetics -- Using Cell Culture Models of Centrosome Amplification to Study Centrosome Clustering in Cancer -- Generation and Purification of Tetraploid Cells -- Anti-Microtubule Drugs.s
Keywords: Life sciences; Cell membranes; Microscopy; Life Sciences; Membrane Biology; Biological Microscopy; Electronic books